Impacts of methanesulfonate on the cloud condensation nucleation activity of sea salt aerosol. (15th March 2019) - Tang, Mingjin; Guo, Liya; Bai, Yao; Huang, Ru-Jin; Wu, Zhijun; Wang, Zhe; Zhang, Guohua; Ding, Xiang; Hu, Min; Wang, Xinming
Abstract: Methanesulfonate, an important oxidation product of dimethyl sulfide, is abundant in marine aerosol particles. However, its impact on the cloud condensation nucleation (CCN) activity of marine aerosol is yet to be elucidated, largely because the CCN activity of methanesulfonate has been seldom investigated. In this work, we measured the CCN activities of three common methanesulfonates, and the single hygroscopicity parameters ( κ ) were determined to be 0.46 ± 0.02 for sodium methanesulfonate (NaMS), 0.37 ± 0.01 for calcium methanesulfonate, and 0.47 ± 0.02 for potassium methanesulfonate, respectively. In addition, we explored the effect of NaMS on the CCN activities of NaCl and synthetic sea salt. It was found that if presented with a mass ratio of 1:1, NaMS would significantly reduce the CCN activities of NaCl and sea salt, and the κ values of binary mixtures could be estimated using the simple mixing rule. Nevertheless, if only presented with a mass ratio of 1:10 (an environmentally relevant value), the effect of NaMS on the CCN activities of NaCl and sea salt was found to be small. Overall, we conclude that from our experimental data and its levels found in the troposphere, methanesulfonate may only have minor impacts on the CCN activity of marine aerosol. Highlights: Methanesulfonate is an important oxidation product of dimethyl sulfide. CCN activities of common methanesulfonates were found to be quite high. Methanesulfonate may only have minor impacts on the CCN activity of marine aerosol.